Clinical and Para clinical characteristics of non-classic Phenylketonuria - Shakiba, Marjan; Saneifard, Hedyeh; Alaei, Mohammad Reza; Mosallanejad, Asieh; lotfi, Mojtaba; yasaei, Mehrdad; Alizade naderi, Elahe (Iranian Journal of Child Neurology, 2021)
Abstract Objective Phenylketonuria (PKU) is one of the most common inherited metabolic diseases, classified as classic and non-classic forms.2% of children with PKU develop a severe and progressive neurologic disease called non classic (malignant) PKU. We aimed to demonstrate the clinical features and laboratory findings and the diagnostic and therapeutic properties of non-classic PKU patients referred to a tertiary level referral center of children in Tehran. Material and Method In this study, we evaluate background information such as gender and age, clinical manifestations, laboratory findings, and response rates to conventional treatment of patients with non-classic PKU who referred to Mofid Children's' Hospital through neonatal screening. Result Twenty patients with diagnosis of non-classic PKU were included. The mean age of them was 6.00 ± 2.81 years ranging from 2 to 12 years, and 45.0% were male. In patients with late diagnosis, the most common presentations were motor developmental delay (15.0%), skin and cutaneous manifestations (15.0%), seizure (5.0%), and restlessness (5.0%). An overall response to treatment was 85.0%. Factors that predict good response to treatment were female gender, higher neopterin level, and lower age at diagnosis and management. Conclusion In conclusion, about half of patients with non-classic PKU remain asymptomatic, which is due to early diagnosis via neonatal screening. Also, higher age at diagnosis and treatment, besides low neopterin levels, may be useful as prognostic factors.